OPTIMIZATION OF SURGICAL TREATMENT OF VESICOVAGINAL FISTULAS - V. L. Medvedev; A. M. Opol’skiy (Вестник урологии, 2017)
Currently, urogenital fistulas are one of the most actual and socially significant problems of medicine. A common type of urogenital fistula is the vesicovaginal fistula. The most difficult for surgery treatment is postradiation vesicovaginal fistula, which appear after uncontrolled radiation exposure on the pelvic. This is due to decrease of tissue vascularization, the prevalence of fibrosis in the lamina, muscle tissue in the vaginal and bladder mucosa, chronic lymphocytic inflammation and hyperkeratosis which destroy epithelium. Conservative therapy of vesicovaginal is not usually effective and in rare case leads to fistula closure. Thus, surgical approach remains the accepted strategy for the treatment of vesicovaginal fistulas. This article contains the most actual literary data with optimal strategy for the treatment of vesicovaginal fistula.